Analysis of Learning Achievement and Teacher–Student Interactions in Flipped and Conventional Classrooms - Sun, Jerry Chih-Yuan; Wu, Yu-Ting (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
This study aimed to investigate the effectiveness of two different teaching methods on learning effectiveness. OpenCourseWare was integrated into the flipped classroom model (experimental group) and distance learning (control group). Learning effectiveness encompassed learning achievement, teacher-student interactions, and learning satisfaction. The experimental method was supplemented with qualitative interviews. Overall, 181 freshmen taking a course on physics were allowed to choose their own class based on their preferred teaching method (experimental or control group). The findings indicated that learners in the experimental group scored higher for learning achievement. When selecting a teaching method, if sufficient resources are available, it is suggested that teachers provide learners with the combination of OCW and flipped classroom. Although there was no significant between-group difference in terms of teacher-student interactions and learning satisfaction, the interactions in the flipped classroom had positive effect on students’ learning achievement. The use of the flipped classroom model allows for adequate teacher-student interactions, as teachers can provide guidance and assistance to students in person, while there are greater opportunities for collaborative learning among learners. In addition, since the flipped classroom model emphasizes the process of learning rather than its outcomes, information technology tools should be used to keep detailed records and follow the learning process in order to assess various aspects of the learners’ growth. The results of this study can serve as a reference for future studies on the flipped classroom model and OpenCourseWare, as well as for teachers and researchers in related fields.